Using Clinical Research Networks to Assess Severity of an Emerging Influenza Pandemic. (8th May 2018) - Simonsen, Lone; Higgs, Elizabeth; Taylor, Robert J; Wentworth, Deborah; Cozzi-Lepri, Al; Pett, Sarah; Dwyer, Dominic E; Davey, Richard; Lynfield, Ruth; Losso, Marcelo; Morales, Kathleen; Glesby, Marshall J; et al.
Abstract: Background: Early clinical severity assessments during the 2009 influenza A H1N1 pandemic (pH1N1) overestimated clinical severity due to selection bias and other factors. We retrospectively investigated how to use data from the International Network for Strategic Initiatives in Global HIV Trials, a global clinical influenza research network, to make more accurate case fatality ratio (CFR) estimates early in a future pandemic, an essential part of pandemic response. Methods: We estimated the CFR of medically attended influenza (CFRMA ) as the product of probability of hospitalization given confirmed outpatient influenza and the probability of death given hospitalization with confirmed influenza for the pandemic (2009–2011) and post-pandemic (2012–2015) periods. We used literature survey results on health-seeking behavior to convert that estimate to CFR among all infected persons (CFRAR ). Results: During the pandemic period, 5.0% (3.1%–6.9%) of 561 pH1N1-positive outpatients were hospitalized. Of 282 pH1N1-positive inpatients, 8.5% (5.7%–12.6%) died. CFRMA for pH1N1 was 0.4% (0.2%–0.6%) in the pandemic period 2009–2011 but declined 5-fold in young adults during the post-pandemic period compared to the level of seasonal influenza in the post-pandemic period 2012–2015. CFR for influenza-negative patients did not change over time. We estimated the 2009 pandemic CFRAR to be 0.025%, 16-fold lower than CFRMA . Conclusions: Data from a clinical research network yielded accurate pandemic severity estimates, including increased severity among younger people. Going forward, clinical research networks with a global presence and standardized protocols would substantially aid rapid assessment of clinical severity. Clinical Trials Registration: NCT01056354 and NCT010561. Abstract : We demonstrate how to use baseline and prospective data from global clinical research networks to rapidly assess the severity of an emerging influenza pandemic.